Public participation in the community planning in China - Jia Shuqian; Cao Kang (AESOP, 2019)
In the 1980s, Chinese scholars in the field of planning began to introduce the theory and experience of Western public participation to China, and meanwhile carried out the practices. After 30 years' development, public participation in Chinese planning is involved in macro --, meso --, and micro levels of planning, namely urban comprehensive planning, control detailed planning, and community planning. Furthermore, more and more attention is paid to the micro level community planning.
Keywords: Community planning; Chinese public participation; Arnstein's ladder theory; Community planners; Multilateral governance